A TOOTH-SUPPORTED TELESCOPIC OVERDENTURE FOR IMPROVED RETENTION AND STABILITY IN COMPROMISED ORAL CONDITIONS - Muhammad Genadi Askandar; Mohd. Dwira Wardhani; Michael Josef Kridanto Kamadjaja (FKG ULM, 2026)
Background: Telescopic overdenture is a removable prosthesis that covers and utilizes remaining teeth as support through a double crown system consisting of inner and outer copings. This type of prosthesis is indicated in cases where several teeth require extraction while others can still be preserved despite compromised periodontal conditions. Its advantages include good long-term prognosis, ease of cleaning, and reduced food retention due to the metal coping surface, which helps maintain periodontal health of abutment teeth. Purpose: To improve esthetics, speech, and masticatory function using telescopic overdenture. Case: A 38-year-old male presented with multiple missing and mobile teeth in both maxillary and mandibular arches. The patient reported discomfort during mastication and decreased self-confidence due to poor dental appearance, and requested prosthetic rehabilitation. Case Management: Initial treatment included scaling and root planing, extraction of teeth 13, 21, 23, 24, 28, 33, and 32, and occlusal adjustment. Transitional dentures were fabricated for both arches as an interim solution. Definitive treatment involved a telescopic overdenture in the mandible and a complete denture in the maxilla. Conclusion: Telescopic overdenture is an effective treatment option for partially edentulous patients, providing improved retention, stability, esthetics, and function while preserving remaining teeth and supporting long-term oral health.Keywords: Double crown, Occlusal force, Periodontal tissue, Splintining teeth, Telescopic denture